High pacing rates for management of aortic insufficiency after balloon aortic valvuloplasty or transcatheter aortic valve replacement. Issue 1 (25th March 2013) - Ali, Omar; Salinger, Michael H.; Levisay, Justin P.; Feldman, Ted
<x xml:space="preserve">Abstract</x> Aortic insufficiency (AI) after transcatheter aortic valve replacement (TAVR) is difficult to manage when associated with congestive heart failure. AI after balloon aortic valvuloplasty (BAV) may be catastrophic, especially in patients who are not candidates for TAVR. We describe the use of urgent temporary pacing, followed by permanent pacing, to increase the heart rate to diminish diastolic filling time for the short term management of AI after BAV or TAVR. The strategy is particularly useful in patients who already have permanent pacemakers, which are common in this population. © 2013 Wiley Periodicals, Inc.